Biometric parameters of some mammals in Kochkor valley - T.I. Imanaliev (Acta Biologica Sibirica, 2019)
Such prominent zoologists as N. A. Severtsov (1877), D. N. Kashkarov (1923–1926), V. N. Shnitnikov (1936), D.P. Dementiev (1938-1955) initiated the study of animals in the Kochkor valley, as well as the territory of  Kyrgyzstan. As a result of their research, the species composition, distribution and biological features of some species of animals were revealed. Based on the above, the relevance of studying the biota of the Kochkor valley was recognized and the purpose of this study was: clarification of mammalian fauna; determination of the biometric parameters of some mammalian species.